Appraisal of Climatic Conditions for Potential Solar Energy Applications in Nawabshah and Quetta Cities - Jakhrani, A. Q.; Jatoi, A. R.; Jakhrani, M. M.; Laghari, A. N.; Kamboh, S. A. (Engineering, Technology & Applied Science Research, 2019)
This study was conducted to appraise climatic conditions for potential applications of solar energy units in Nawabshah and Quetta cities. For that, twenty two annual monthly average data of insolation on horizontal surface, at various slopes on titled surface, air temperature, earth skin temperature was acquired and evaluated through the Statistical Package for the Social Sciences software. It is discovered from the study that Quetta is a more promising place for installation of solar energy applications as compared to Nawabshah as it receives more solar radiations and less air temperature.